Information System For Fieldwork Practices At The Cikampek Community Eye Center - Eka Chandra Ramdhani; Haris Ardiansyah; Asep Asep; Juniarti Eka Sapitri; Fransisca Natalia (Journal of Information System, Informatics and Computing, 2022)
Field Work Practice is a form of educational service combined the vocational and vocational training, which is usually followed by students or university students by working directly in the business world or the industrial world, systematically and directed with competent supervision in their fields with the aim of gaining experience and skills in mastering expertise in all fields to reach a certain level of professional expertise. At the Cikampek Public Eye Health Center (BKMM), the registration mechanism, submission to reporting of fieldwork practices are still carried out in a paper-based and must go directly to the BKMM Cikampek office, from these problems, a web-based fieldwork practice Information System is needed, with the hope that this system could help manage and process information data from all related entities to be more effective and efficient. This PKL Information System development method uses a prototype method starting from analysis, design, coding the system, system testing, system evaluation, and system implementation so as to produce a computerized information system that can speed up the data processing process, efficiency in cost management and more accurate information produced.